FFAKTOR INTRINSIK YANG MEMPENGARUHI MOTIVASI PETANI JAHE PADA MASA PANDEMI COVID-19 DI KECAMATAN PORSEA KABUPATEN TOBA - Wella Tessalonika Ambarita; Nur Syamsiyah; Trisna Insan Noor; Sulistyodewi Nur Wiyono (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Ginger (Zingiber officinale) is a medicinal plant that has many health benefits. During the COVID-19 pandemic, the demand for ginger in the market has increased. Therefore, ginger production must be increased to supply consumer demand. High production is inseparable from the motivation of farmers to develop their farming. Motivation is a condition that encourages a person to take an action that is influenced by internal factors (intrinsic factors). The purpose of this study was to determine the intrinsic factors that influence the motivation of ginger farmers during the COVID-19 pandemic. This study uses a qualitative design with a survey method. The location of the research was determined using a purposive technique. The research was conducted in Amborgang Village and Nalela Village for consideration as a center for ginger production in Porsea District. The research population is ginger farmers with a total of 160 people. The research sample was taken using probability sampling technique. The number of samples was 62 people consisting of 41 people from Ambogang Village and 21 people from Nalela Village. Data collection is done by observation, interviews, and documentation. The analysis technique used is descriptive analysis. Respondents are dominated by productive age around 95.16 persen, male sex around 93.55 persen, high school education graduates around 58.06 persen, and main occupation as farmers around 77.42 persen. The results showed that the intrinsic factor was in medium category with a score percentage is 55.16 persen. The variables of formal education and experience are in high category; variables of age, income, land area, and number of family are in medium category; and variable of non-formal education is in low category.